Validation of a fully automated chemiluminescent immunoassay for cattle serum and plasma progesterone measurement - Megahed, Ameer A.; Jones, Kristi L.; Bisinotto, Rafael S.; Chebel, Ricardo C.; Galvão, Klibs N.; Chan, Ann M.; Bittar, João H. J. (Frontiers in Veterinary Science, 2023)
Introduction Monitoring circulating progesterone concentration ([P4]) is an important component of basic and applied reproduction research and clinical settings. IMMULITE® 2000 XPi (Siemens Healthineers, Cary, NC) is a newly upgraded fully automated immunoassay system marketed for human use to measure concentrations of different measurands including P4. Objectives Our objective was therefore to characterize the analytical performance of the IMMULITE® 2000 XPi P4 immunoassay (IPI) across the reportable range in serum and plasma of cattle. Methods The IPI validation protocols included characterization of the method linearity, within-run, and between-run precision through calculation of the coefficient of variation (CV). The method accuracy was assessed through the calculation of the spiking-recovery (SR) bias across the reportable range (0.2–40.0 ng/mL). Passing–Bablok regression and Bland-Altman plots were used to determine the interlaboratory bias for two laboratories. Three types of observed total error (TEo) were calculated based on the considered type of bias, TEoSR (spiking-recovery), TEoRB (range-based bias), and TEoAB (average-based bias). Results The IPI was linearly related to the true value (R2 = 0.997) across the reportable range. The within-run and between-run precision (CV%) of the IPI for both serum and plasma [P4] of clinical relevance (1, 2, 5, and 10 ng/mL) were <5 and <10%, respectively. The TEo reported here for serum and plasma at [P4] of 1 and 5 ng/mL was ~20 and 25%, respectively. Of interest, the three types of TEo were relatively similar regardless of the considered bias. Conclusions We concluded that the automated IPI provides a precise, accurate, reliable, and safe method for measuring [P4] in both serum and plasma of cattle. Consistent with the manufacturer's recommendations, the serum matrix is more accurate than plasma.